Nursing care quality: a concept analysis - Koy, Virya; Yunibhand, Jintana; Angsuroch, Yupin (International Journal of Research in Medical Sciences, 2017)
The purpose of this paper is to provide a clear definition of nursing care quality that contributes to the formulation, application, and measurement of quality nursing outcomes for patients, organisations, and nursing staff. It also indicates the manner in which, by using the definition, empirically based operational definitions can be developed for different operational environments and settings. The study employed a concept analysis methodology to extract terms, attributes, antecedents, and consequences (outcomes) from relevant literature databases. The analysis identified nine attributes: nurse competency performance, met nursing care needs, good experiences for patients, good leadership, staff characteristics, preconditions of care, physical environment, progress of nursing process, and cooperation with relatives. Antecedences include nurse-staffing levels, positive practice environment, and nursing turnover. Consequences include patient safety, patient satisfaction, nursing outcomes, nurse satisfaction, and budget management. Because of the breadth and depth of modern nursing practice, further research and development of the concept is required.